NARROWING THE DIGITAL DIVIDE IN MALAYSIA: ISSUES AND INITIATIVES - L.N. Foo; W.K. Lai; C. Elamzazuthi (Universitas Gadjah Mada, 2002)
Equity of and access to information and communication technologies (ICT) is currently a burning issue in many countries around the world. Malaysia, as a nation with about 22 million inhabitants, has taken some strong strides in recent times to bridge the access and equity gaps through appropriate policies and strategic national programmes. This paper will examine some of the key elements of several of these initiatives to bridge the digital divide in the country, in particular, the Titian Digital programme. We will also be identifying some of the major challenges that this programme hopes to resolve.